EFFECT OF ACTIVATED CHARCOAL ADDITION ON FORMALDEHYDE EMISSION OF MEDIUM DENSITY FIBERBOARD - Darmawan, Saptadi; Sofyan, Kurnia; Pari, Gustan; Sugiyanto, Krisdianto (Secretariat of Forestry Research and Development Agency, 2010)
The manufacturing of medium density fiberboard (MDF) using dry forming process for interior purpose requires extensive amount of thermo-setting urea formaldehyde (UF) adhesive. Unfortunately, this adhesive brings about formaldehyde emission from the resulting MDF, which was potentially harmful to human beings. The use of activated charcoal can be effective to reduce such emission. As the relevance, this research aimed to investigate the effect of activated charcoal addition to the MDF pulp on formaldehyde emission from the MDF. The fibers for the MDF-mat forming were the pulp procured from the MDF factory, resulting from the thermo-mechanical pulping (TMP) conducted on the mixed mangium wood (Acacia mangium) and rubber wood (Hevea brasiliensis) in 3:1 (w/w) proportion, respectively. Such mixed TMP pulping was also done in the factor y. The bonding between TMP pulp fiber during mat forming was assisted by the use of UF adhesive. Prior to the MDF mat forming , was added to the resulting TMP pulp-fibers activated charcoal in various amount, 2%, 4% and 6% based on fiber mass as well as based on UF adhesive mass. The activated charcoal was prepared by carbonizing candle nut shell into charcoal followed by activation process using phosphate solution. Meanwhile the forming of MDF mat employed air-dr y process. As the control, MDF forming with UF adhesive was performed without addition of activated charcoal. It turned out that the activated charcoal-added MDF exhibited effective reduction in formaldehyde emission and significant improvement in physical and mechanical properties, i.e. lower thickness swelling , and greater MOR , MOE and internal bond, compared to the control MDF. The use of activated charcoal at 4% based on the adhesive mass seemed to be the optimum amount. Physical and mechanical properties of the activated charcoal added MDF could mostly meet the JIS specification.